Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Produk 1001 Beras Pada PD. Ega Rasa Garut - Mulyana, Tatang (Jurnal Wacana Ekonomi, 2017)
This research aims to determine product quality and service quality of customer satisfaction either partially or simultaneously. With 7 dimensions of product quality that is performance, durability conformance of sfecifications, realibility, aesthetics, perceived quality, and serviceability. And the dimensions for service quality are reliability, responsiverness, assurance, tangible, and emphaty, as for the dimensions of the customer satisfaction of the received performance, expektasi, and loyalitas. The method of analysis used in this research is descriptive method. Sample in this research counted 98 people. This sampling method uses ease of sampling technique. Because the number of populations is not known for size of the sample that is using the formula calculations. Unknown populatins. The analysis technique used, the writer looks for the simultaneous and partial relationship between product quality, service quality and customer satisfaction by using quantitative analysis technique in the form of reliability test data and using multiple linier regression analysis, significant test and test determination. The result of simultaneous research shows that there is influence of product quality and service quality to customer satisfaction, where the variable x1 and x2 plays an impormant role in building of forming customer satisfaction in the customer?s mind.